Antibacterial Activity Test of Ethanol Extract of Basil Leaves (Ocimum basilicum) Against Streptococcus mutans and Porphyromonas gingivalis - Soamole, Nurul Fatimah; Nuryanti, Siska (Journal Microbiology Science, 2024)
Basil leaves (Ocimum basilicum) is a type of plant used traditionally that has antibacterial potential. Antibacterial compounds are compounds that can inhibit the growth of bacteria. This study aims to obtain ethanol extract of basil leaves (Ocimum basilicum) to determine the activity and diameter of the largest inhibition zone against Streptococcus mutans and Porphyromonas gingivalis bacteria. This research was started by preparing a thick extract of basil leaves which was obtained by extracting basil leaves by maceration. Antibacterial screening test with concentrations of 0.1% and 0.5% against Streptococcus mutans and Porphyromonas gingivalis. The method used was agar diffusion with 6 concentrations in each treatment group of ethanol extract of basil leaves with concentrations of 0.5%, 1%, 5%, 10%, 15% and 30%. The results of the screening test gave activity at a concentration of 0.5% against the two test bacteria. The results of the antibacterial activity test of the ethanol extract of basil leaves against the test bacteria obtained the largest diameter of the inhibition zone at a concentration of 30%. Based on research, the ethanol extract of basil leaves has activity as an antibacterial.